El nexo copulativo en húngaro y en español - Rózsavári, Nóra (Verbum – Analecta Neolatina, 2010)
The Hungarian verb van ‘to be' may be rendered in Spanish by two verbs: ser and estar. The translation of van depends on the structure in which these two verbs appear. When the copula is followed by a noun, pronoun or the preposition de and a noun, there is an obligatory use of ser. It is used without a preposition to identify or to classify. When it classifies, it can take the preposition de. Estar always takes a preposition. It may indicate the function performed by the subject or it may indicate various other things depending on the preposition. When the verb is followed by an adjective, ser expresses a permanent or inherent quality, estar expresses a quality which is neither permanent nor inherent. Sometimes both verbs may be used with the same adjective, but there is a change of meaning.